2016
DOI: 10.1002/acn3.292
|View full text |Cite
|
Sign up to set email alerts
|

Ambroxol chaperone therapy for neuronopathic Gaucher disease: A pilot study

Abstract: ObjectiveGaucher disease (GD) is a lysosomal storage disease characterized by a deficiency of glucocerebrosidase. Although enzyme‐replacement and substrate‐reduction therapies are available, their efficacies in treating the neurological manifestations of GD are negligible. Pharmacological chaperone therapy is hypothesized to offer a new strategy for treating the neurological manifestations of this disease. Specifically, ambroxol, a commonly used expectorant, has been proposed as a candidate pharmacological cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
167
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(173 citation statements)
references
References 35 publications
2
167
1
3
Order By: Relevance
“…While recombinant GCase administration restored the number of lysosomes, this effect was enhanced when TFEB was overexpressed (Awad et al., ). The purported pharmacological chaperone ambroxol was shown to increase the expression of TFEB, as well as several lysosomal genes including GCase (McNeill et al., ; Narita et al., ).…”
Section: Modifiers Of Gaucher Disease: Results Of Candidate Gene Studiesmentioning
confidence: 99%
“…While recombinant GCase administration restored the number of lysosomes, this effect was enhanced when TFEB was overexpressed (Awad et al., ). The purported pharmacological chaperone ambroxol was shown to increase the expression of TFEB, as well as several lysosomal genes including GCase (McNeill et al., ; Narita et al., ).…”
Section: Modifiers Of Gaucher Disease: Results Of Candidate Gene Studiesmentioning
confidence: 99%
“…Chaperones can cross the blood-brain barrier and selectively bind to misfolded glucocerebrosidases facilitating the correction of protein misfolding and improving enzyme function. A recent pilot study investigating the efficacy of PCT in patients with Type III GD reported marked improvements in saccadic initiation latency and pupillary light reflex dysfunction107 using chromatic pupillometry device 108. Future studies should evaluate the efficacy of PCT in treating ophthalmic manifestations of GD.…”
Section: Discussionmentioning
confidence: 99%
“…The potency of ambroxol for GD has been demonstrated in various in vitro and in vivo models such as cells, mice, and flies (Luan et al, 2013; Maor et al, 2016). Pilot studies conducted in 12 patients with GD type 1 and five with neuronopathic GD demonstrated no further deterioration of clinical symptoms in the patients with GD type 1 and improvement of myoclonus and pupillary light reflex in patients with GD type 3 (Narita et al, 2016; Zimran et al, 2013). In an in vitro study where α-syn was reduced in an ambroxol-treated α-syn over-expressing neuroblastoma cell line and preliminary reports of the efficacy of ambroxol in neuronopathic GD, support further study of this molecule (McNeill et al, 2014).…”
Section: Therapeutics For Gaucher Disease May Also Impact Parkinson Dmentioning
confidence: 90%